2023
DOI: 10.1021/acsaom.3c00243
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Optical, Nonlinear Optical, Thermal and Terahertz Time Domain Spectra of l-Histidine Single Crystal: A Potential Terahertz Material

Sudha Yadav,
Mukesh Jewariya,
Manju Kumari
et al.

Abstract: Nonlinear optical (NLO) single crystals have become very useful for second harmonic generation, fiber-optic communications, electro-optic modulation techniques, terahertz (THz) wave generation and detection, and other numerous applications. Researchers exploring crystals need to identify appropriate NLO materials in order to achieve the aforementioned objectives. In the present work, crystals of l-histidine (LH), which is an amino acid, were successfully grown by a slow evaporation technique over a period of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The desired frequency of THz radiation is realized 2.29 10 Hz. 13 ´The equilibrium plasma density is considered to be 1.5 10 cm . 17 3…”
Section: = =mentioning
confidence: 99%
See 1 more Smart Citation
“…The desired frequency of THz radiation is realized 2.29 10 Hz. 13 ´The equilibrium plasma density is considered to be 1.5 10 cm . 17 3…”
Section: = =mentioning
confidence: 99%
“…In the context of the development of THz technology, the recent contributions of various research groups have significantly advanced the understanding of the generation of THz waves and their applications. Yadav et al [13] successfully demonstrated the suitability of a sizable crystal of L-Histidine for THz applications, which remarkably exhibits thermal stability up to 275.5 °C, possesses a band gap of 4.4 eV, and exhibits frequency absorption spectra in the range of 0.8-2.5 THz. Zhang et al [14] reported the design of a highly efficient THz detector incorporating a Tamm cavity, which involves an embedded detector chip within a multilayer Si/air Distributed Bragg Reflector (DBR) for significant enhancement of the strength of the THz signal.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz-Time Domain Spectroscopy (THz-TDS) analysis is performed to access the electronic behavior of the molecules in THz region. Numerous organic materials exhibit promising potential for applications in NLO techniques, such as N-benzyl-2-methyl-4-nitroaniline (BNA), 4-N,Ndimethylamino-4 ′ -N ′ -methyl-stilbazolium tosylate (DAST), and 4-N,N-dimethylamino-4 ′ -N ′ -methyl-stilbazolium 2,4,6trimethylbenzenesulfonate (DSTMS) [19]. These materials are particularly active NLO materials and are frequently employed in techniques like difference frequency generation and optical rectification to generate THz waves.…”
Section: Introductionmentioning
confidence: 99%